The Reform Movement in a long-winded student journal (2018)
The present study analyzes a long-standing Argentine student journal called Verbum that belonged to the Philosophy and Letters Student Center of the University of Buenos Aires (CEFYL). Through its content, we propose to give an account of the image of that institution and its reformist movement between 1912 and 1942. The faculty of humanities is presented as an Olympic temple of knowledge with different limitations: little operational budget, invalidity of its titles, disqualified teachers, lack of occupational projection in the national culture. However, the existence of great intramural figures such as José Ingenieros or Ricardo Rojas stands out. On the other hand, it was there where the first actions of reformist leaders took place, for instance, those of Gregorio Bermann, who became a specialist in student movements and was the author of the book La juventud de América de la UNAM. From Verbumand the environment of the faculty emerged a range of similar and contradictory positions that reduced the reformist platform to purely didactic and guild demands or that extended it to the civil, community and international terrain. That is why we address here the work of avant la lettrereformers like Bermann, intellectuals within the reformist movement, such as Coriolano Alberini, or anti-reformists as Leopoldo Lugones. Within the Faculty of Philosophy and Letters was recurrent the citation of diverse political-academic positions, that appealed to the reformist nominal emblem, beyond its commitments with all the flags raised by the Reformation. From these positions arises the Partido Reforma Universitaria. In short, the reformist identity has been a broad ideological spectrum, applicable to all those who agree with progressive nominations from different degrees of radicalization and distanced both from ultramontane traditionalism and liberal conservatism. The methodology of this study attempted to adapt the guidelines of Noemí Girbal for the entry "Journals" in the Dictionary Pensamiento Alternativo, Adenda.